Environmental and financial benefits of improved cookstove technologies in the central highlands of Ethiopia - Negash, Dugassa; Abegaz, Assefa; Smith, Jo U. (Biomass & bioenergy, 2021)
This study assessed the potential contributions of improved cookstoves in increasing organic fertilizer availability for application to farmland, greenhouse gas emission mitigation and improvement of household finances using the Kitchen Performance Test, Controlled Cooking Test, household survey and focus group discussions. Substitution of a three-stone open fire with improved cookstoves significantly (p < 0.01) improved fuel use efficiency by 54% (highest) for the mirt stove with an additional biogas stove and 32% (lowest) for the mud stove without an additional biogas stove. The greenhouse gas emission reductions in carbon dioxide equivalents were 4534 (±32) kg y−1, 6370 (±42) kg y−1, 6953 (±51) kg y−1, 7661 (±43) kg y−1 for the mud stove, mirt stove, mud stove with an additional biogas stove and mirt stove with an additional biogas stove respectively. The average financial savings from the sale of surplus biomass fuel for the improved cookstoves were higher than the summed financial savings from substitution of commercial fertilizer, generation of carbon finance and replacement of kerosene for lighting. This explains why households usually prefer to sell surplus biomass fuels instead of using them as organic fertilizers. This finding suggests that wide scale adoption of fuel-efficient solid biomass stoves can contribute to the financial security of households, and may help to reduce green gas emissions, but will do little to increase the fertility of soils. By contrast, including biogas stoves will help to improve soil fertility by retaining at least some of the carbon and nutrients in bioslurry that will then be applied to the soil. •Improved stoves significantly (P < 0.01) increased biomass fuel use efficiency.•Cookstoves met minimum GTZ efficiency standard (40%) for carbon financing.•Solid biomass stoves contribute to financial security & reduction of deforestation.•Solid biomass stoves do little to increase soil fertility if used without biogas.